CITY COMPETITIVENESS - Kamal, Madiha; Aijaz, Urooj; Shafiq, Dr. Hina; Mushtaq, Naila; Khan, Khalid; Rauf, Fawad; Qureshi, Humza (The journal of contemporary issues in business and government, 2021)
By the year 2025 over half of the global growth will be contributed by 577 “middle weight” cities in the top 600 and the vast majority of them will be in emerging economies, and two-thirds from Chinese and Indian cities. Accordingly, “Urbanization and economic growth are strongly associated, hence, urban areas, in general, and cities, in particular, have been identified as the “Engine of Growth”, and “Agent of Change” (Mohan and Das Gupta, 2005). Cities evolve multiplicity of opportunities that allow individuals and communities to come together and exercise multifarious activities. The concept of “creative-cities” is rapidly attracting the interest of academician and policy makers. By 2020, over 60 percent of the China’s population will be living in cities. It is estimated, that, by 2050, about 67 percent of the world’s population will be city dwellers (6.3 billion people). This would be 8.3 billion people by the early 22nd century. Cities produce over 80 percent of the world’s GDP and, 60 percent of the world’s GDP is being generated by top 600 cities with 25 percent of the world’s population. Such high economic density reflects the vital role of cities as the main source of productivity. There has been no systematic research exists in the country to identify the relative importance of the “Key drivers of city competitiveness. Present endeavor, for the first in Pakistan, an exploration in this direction.